Pengaruh Kepemimpinan Kepala Desa dan Pengetahuan Perpajakan Terhadap Kepatuhan Masyarakat Dalam Membayar Pajak Bumi dan Bangunan (Studi Kasus Desa Tunggulwulung Kecamatan Pandaan Kabupaten Pasuruan) - Nafida Hilda Ramadhani; Dwiyani Sudaryanti; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
The purpose of this study was to determine the influence of village head leadership, tax knowledge on community compliance in paying land and building taxes. This research method uses quantitative research with a Likert scale 5 questionnaire data collection technique to the community in Tunggulwulung Village, Pandaan District, Pasuruan Regency. For data analysis methods using multiple linear regression analysis. This study used a sample of 97 based on the slovin formula. based on the results obtained by the researcher, it can be proved that the village head's leadership and knowledge of taxation have a positive effect on community compliance in paying land and building taxes, which means that the higher the village head's leadership and knowledge of taxation, the higher the community's compliance in paying land and building taxes in the Tunggulwulung Village, District Pandaan, Pasuruan Regency.Keywords: Village head leadership, tax knowledge, community compliance in paying land and building taxes